Linearized Morison Drag for Improvement Heave Response of Semi-Submersible by Diffraction Potential - Koto, Jaswar; Abyn, Hassan; Khairuddin, N. M.; Siow, C.L. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This research is targeted to improve the semi-submersible heave response prediction by using diffraction potential theory by involving drag effect in the calculation. The comparison to the experimental result was observed that heave motion tendency predicted by the diffraction potential theory is no agreed with motion experimental result when the heave motion is dominated by damping. In this research, the viscous damping and drag force for heave motion is calculated from the drag term of Morison equation. The nonlinear drag term in Morison equation is linearized by Fourier series linearization method and then inserted into the motion equation to correct the inadequate of diffraction potential theory. The proposed numerical method is also applied to simulate the semi-submersible motion response to obtain the heave motion tendency predicted by this numerical method. In comparison to the experimental result which tested at the same wave condition obtained that the diffraction potential theory with the Morison drag term correcting is able to provide satisfying heave response result especially in damping dominated region.